Criminal Sanctions and Personal Data Protection in Indonesia - Kukuh Dwi Kurniawan; Deassy J. A. Hehanussa; Rahmat Setiawan; Indah Susilowati; Sopian; Desmarani Helfisar (APPTHI, 2024)
This research analyzes Indonesia's Law Number 27 of 2022 on Personal Data Protection (Law on Personal Data Protection), focusing on its regulatory framework and institutional strengthening efforts. The study employs a normative legal research approach with a descriptive-analytical method, examining primary legal materials such as Law Number 27 of 2022 and secondary sources including relevant academic literature. To provide a global perspective, comparisons are drawn with the General Data Protection Regulation (GDPR) in the European Union, the Personal Data Protection Act (PDPA) in Singapore, and the Act on the Protection of Personal Information (APPI) in Japan. The findings reveal that while the Law on Personal Data Protection provides a comprehensive framework for personal data protection, its implementation faces significant challenges, including low public awareness, insufficient readiness in the business sector, and limited enforcement capacity of supervisory institutions. Strengthening institutional frameworks and enhancing public understanding of data privacy rights are critical steps toward addressing these challenges. Although criminal sanctions are stipulated in the law, their application has yet to be evaluated in depth, as this research primarily focuses on regulatory analysis. Suggestions include developing robust technological and organizational measures to secure data and fostering international collaboration in managing cross-border data flows to align with global standards. Further research is recommended to assess the effectiveness of criminal sanctions in deterring data breaches and their role in enhancing the overall efficacy of Indonesia's personal data protection framework.